RANCANGAN MOTIF KAIN POLA GARIS SIMETRIS MODEL FRAKTAL DENGAN EMPAT DAN LIMA KOMPONEN COLLAGE GARIS DAN PERSEGI-EMPAT - Resta Ari Sandi; Tommy Irsyad Najib; Tedjo Darmanto (STKIP PGRI Situbondo, 2024)
The motif pattern of cloths can be designed in fractal form based on Collage components composition by means of the iterated function system (IFS) encoding algorithm to encode the design position into a code and decoding algorithm to decode the code and to display the fractal object. In this paper, two kinds of Collage component composition in straight lines and self-similarity feature are discussed. The first model consists of four lines and one square shape of Collage component. The second model consists of three lines and one square shape of Collage component. The composition is made in a such way, that there are several closed planes to be colored later. The IFS code generated by the IFS encoding algorithm is normalized to ensure that the straight lines are crossed to one or two neighbor lines in the right position and the self-similarity feature is also fitted to fill the void and integrated with the lines